Hydroxysafflor yellow A alleviates oxidative stress and inflammatory damage in the livers of mice with nonalcoholic fatty liver disease and modulates gut microbiota - Wu, Liang; Dong, Xueyun; Sun, Wen; Jiajun, Tan; Ali, Asmaa; He, Jiayuan; Wang, Pingping (Frontiers in Pharmacology, 2025)
IntroductionHydroxysafflor yellow A (HSYA), its primary bioactive metabolite of Carthamus tinctorius L. (safflower), has shown therapeutic potential in various inflammatory diseases. However, its role in alleviating inflammation and oxidative stress in non-alcoholic fatty liver disease (NAFLD) remains unclear. This study investigates the therapeutic effects of HSYA in mice with NAFLD, focusing on its impact on gut microbiota and serum non-targeted metabolomics to elucidate the mechanisms underlying its efficacy.MethodsNAFLD was induced in mice using a high-fat diet (HFD), followed by intragastric administration of hydroxysafflor yellow A (HSYA). Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), and triglycerides (TG) were quantified to evaluate liver function and lipid metabolism. Oxidative stress markers, including superoxide dismutase (SOD) activity and malondialdehyde (MDA) concentration, were also assessed. The pro-inflammatory cytokines IL-6, TNF-α, and IL-1β in serum were measured using ELISA. The hepatic expression of NLRP3 inflammasome and its downstream effector, Caspase-1, was analyzed by Western blot. Histopathological examination of liver tissues was performed using hematoxylin and eosin (H&E) staining to evaluate structural damage. Furthermore, alterations in the gut microbiota composition were characterized via 16S rDNA sequencing of fecal samples. Untargeted metabolomics was conducted to identify serum metabolic variations and elucidate enriched metabolic pathways associated with HSYA treatment.ResultsHSYA significantly inhibited HFD-induced weight gain and alleviated liver inflammation. It reduced serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and triglycerides (TG) (P < 0.05). HSYA administration decreased hepatic mRNA and protein expression of nucleotide binding oligomerization domain like receptor protein 3 (NLRP3), Caspase-1 and interleukin - 1β (IL-1β) while increasing superoxide dismutase (SOD) activity (P < 0.05). Gut microbiota analysis revealed a significant increase in the abundance of Turicibacter, while a reduction of Ruminococcus. Serum metabolomics identified a reduction in inflammation-associated metabolites, such as phenylalanine and tyrosine, alongside enhanced phenylalanine and tyrosine biosynthesis pathways.DiscussionHSYA demonstrates potent anti-inflammatory and antioxidant effects, effectively mitigating liver inflammation and oxidative stress in NAFLD mice. Its therapeutic mechanisms may involve modulating gut microbiota and regulating serum phenylalanine and tyrosine metabolism, offering insights into its potential as a treatment for NAFLD.